Fabrication of mesoporous double-layer antireflection coatings with near-neutral color and application in crystalline silicon solar modules. (1st May 2020) - Xu, Yunfei; Zhang, Jing; Ai, Ling; Lou, Xueqin; Lin, Shenghua; Lu, Yuehui; Fan, Bin; Jin, Jing; Song, Weijie
Highlights: We fabricated the DLAR coatings, consisting of a dense silica bottom and a mesoporous top layers. The proposed DLAR coatings exhibited a near-neutral color under both normal and oblique incidences. The DLAR coatings keep stable after experiencing abrasion and damp heat tests. The DLAR coatings increased the PCE of the c-Si mini-modules by 2.40% in relative terms. The DLAR coatings enable the c-Si mini-modules to achieve a natural and sheer-black appearance. Abstract: Single-layer antireflection (SLAR) coatings have been applied in crystalline silicon solar modules for a decade, which evolved from open-pore silica at an early stage into closed-pore structures nowadays in industry. For improving photovoltaic and aesthetic characteristics of solar modules, not only AR properties but also color neutrality of AR coatings need to be intensively studied. In this work, the double-layer antireflection (DLAR) coatings were designed and their residual color was studied by comparing with conventional SLAR and DLAR coatings under both normal and oblique incidences. According to the design, we fabricated the mesoporous DLAR coatings, which exhibited a high average transmittance of T ave  = 99.02% at visible wavelengths from 380 nm to 780 nm and a low chroma value of C  = 3.35. Applying the mesoporous DLAR coatings to the crystalline silicon mini-modules, the power conversion efficiency was increased by 2.40% on average in relative terms. Besides the power output gain, durable DLAR coatings with neutral color are of great significance for not only imparting a natural and sheer-black appearance to photovoltaic modules without unwanted blueish color, but also finding practical applications in consumer electronics, building glazing, and display windows.